(untitled) (Proceedings of Southern Federal University. Philology, 2020)
Public signs which manage people’s behaviour in public places are an integral part of the linguistic landscape of any city. They not only reflect the existing system of social values, cultural norms and standards, but also play a role in their formation by exerting unconscious and repeated influence on the mentality of citizens. The article examines the linguistic and sociocultural features of the texts of Chinese public signs. The tendencies to soften communicative intent in the texts of public signs, to implement the principle of courtesy, to reject ready-made formulas and clichés, to use the implicit forms of inducement intent expression are noted. Keywords: China, linguistic landscape, public signs, prescriptive, requestive, suggestive. DOI 10.18522/1995-0640-2020-1-93-102